Influence of Reactor Design on the Electrochemical Oxidation and Disinfection of Wastewaters Using Boron-Doped Diamond Electrodes - Salazar-Gonzalez, R; Sandoval, A; Sandoval, A; Calzadilla-Aguiar, W; Calzadilla-Aguiar, W (Elsevier B.V., 2022)
Electrochemical oxidation is the most popular electrochemical advanced oxidation process within the scientific community owing to its simplicity and high effectiveness to treat different wastewaters. Electrode material and reactor design are important factors that influence the removal efficiency of pollutants. This work presents an overview of recent applications of electrochemical oxidation process for contaminant mineralization and water disinfection using electrochemical reactors, in batch and continuous mode of operation, fitted with boron-doped diamond electrodes. In addition, recent advances in the use of flow-through reactors (continuous single-pass and recirculation) are presented. Geometrical aspects, operating conditions, and energy consumption are provided and discussed. © 2022 Elsevier B.V.
Keywords: Electrochemical oxidation; Water disinfection; Wastewater treatment; Boron-doped diamond electrodes; Reactor design